A randomized, controlled study to assess the conversion from calcineurin-inhibitors to everolimus after liver transplantation: PROTECT - Fischer, Lutz; Schemmer, Peter; Schmidt, Jan (American journal of transplantation, 2012)
Posttransplant immunosuppression with calcineurin inhibitors (CNIs) is associated with impaired renal function, while mTor inhibitors such as everolimus may provide a renal-sparing alternative. In this randomized 1-year study in patients with liver transplantation (LTx), we sought to assess the effects of everolimus on glomerular filtration rate (GFR) after conversion from CNIs compared to continued CNI treatment. Eligible study patients received basiliximab induction, CNI with/without corticosteroids for 4 weeks post-LTx, and were then randomized (if GFR > 50 mL/min) to continued CNIs (N = 102) or subsequent conversion to EVR (N = 101). Mean calculated GFR 11 months postrandomization (ITT population) revealed no significant difference between treatments using the Cockcroft-Gault formula (−2.9 mL/min in favor of EVR, 95%-CI: [−10.659; 4.814], p = 0.46), whereas use of the MDRD formula showed superiority for EVR (−7.8 mL/min, 95%-CI: [−14.366; −1.191], p = 0.021). Rates of mortality (EVR: 4.2% vs. CNI: 4.1%), biopsy-proven acute rejection (17.7% vs. 15.3%), and efficacy failure (20.8% vs. 20.4%) were similar. Infections, leukocytopenia, hyperlipidemia and treatment discontinuations occurred more frequently in the EVR group. No hepatic artery thrombosis and no excess of wound healing impairment were noted. Conversion from CNI-based to EVR-based immunosuppression proved to be a safe alternative post-LTx that deserves further investigation in terms of nephroprotection.